The development of an online questionnaire for end users about the visual perception of informational ergonomics and its attributes in graphic brands - da Silva, João Carlos Riccó Plácido [UNESP]; Paschoarelli, Luis Carlos [UNESP]; Friso, Valéria Ramos [UNESP]; da Silva, José Carlos Plácido [UNESP] (Springer Nature, 2019)
The ultimate goal of graphic development is a more effective interface and better end-user understanding. For this, several methods and theories were developed to give support to the graphic developers in this task, but these are not measured in scientific evaluative form, being supported by conventions. A scientific method is needed to understand how the user assimilates the message developed in a graphic object by the designer. This study focuses on graphic objects developed with a method based only on informational ergonomics. The resulting graphic marks were presented to end users in an online questionnaire that raised their impressions, allowing them to cross-reference the data with the attributes considered in the development. The results showed a correct presentation of the items requested in the briefing by the experimental group, which used the method directed to the development of these graphic brands.
Keywords: End user; Graphic marks; Information ergonomics; Questionnaire; Visual perception